Jobcoaching–Example of Good Practice - Małgorzata Anna Dobrowolska (Forum Oświatowe, 2013)
The article discusses the idea of ​​jobcoaching, particularly focused on the Dutch approach – the country where jobcoaching has been described and applied in its full version and adapted to other countries. Jobcoaching is currently the most widely used instrument to combat unemployment among labour market institutions, social assistance and integration. Jobcoaching methodology is described based on a project financed by the European Social Fund with a transnational component for women inmates in penitentiary establishments, as an example of good practice.